Pengembangan Media Website Berbasis Google Sites pada Materi Statistika Kelas IV Sekolah Dasar - Ni Luh Gede Sulistyawati; I Made Suarjana; I Made Citra Wibawa (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The background of the research is that the utilization of available technology is not optimal. The purpose of the study was to determine the validity of the website and to determine the effectiveness of the website based Google Sites on Mathematics subjects in the statistics of fourth grade elementary school students. This research is a development research using the ADDIE model. Data collection methods used, namely the method of observation, interviews, questionnaires, and written tests. The data analysis techniques used were qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistical analysis. The results of the research, namely (1) Google Sites has validity with: the results of the assessment of the two material experts 93% with very good qualifications, the results of the assessments of the two learning design experts with very good qualifications, the results of the assessment of the two learning media experts with 92% very good qualifications, 95.5% individual test results with very good qualifications, 92.5% small group trial results with good qualifications, and 91.8% field test results with good qualifications. (2) Based on the results of the Google Sites it was found that tcount (2.25) > ttable (2.10). This shows that the Google Sites has a significant influence on improving student learning outcomes.